2011
DOI: 10.1113/expphysiol.2011.059360
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in rat mesenteric artery after regional cardiac ischaemia–reperfusion

Abstract: In most previous studies, ischaemia-reperfusion (I/R)-induced vascular injury referred to injury in the tissue or blood vessel that was directly subjected to I/R. However, less attention has been focused on remote vascular injury that might be caused by cardiac I/R. In the present study, we aimed to assess whether cardiac I/R could affect vasoconstriction and vasodilatation in mesenteric arteries from Sprague-Dawley rats. Left anterior descending coronary arteries from adult male Sprague-Dawley rats were occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…More intriguingly, cardiac I/R causes not only myocardial but also vascular injury [ 56 ]. It has also been proposed that reperfusion induced endothelial dysfunction, characterized by decreased endothelium-dependent vasodilatation [ 57 ]. Studies have displayed a potential role of ROS in endothelial dysfunction [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…More intriguingly, cardiac I/R causes not only myocardial but also vascular injury [ 56 ]. It has also been proposed that reperfusion induced endothelial dysfunction, characterized by decreased endothelium-dependent vasodilatation [ 57 ]. Studies have displayed a potential role of ROS in endothelial dysfunction [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the equilibration period, the contractile capacity of each ring was tested by exposure to a high-K þ Krebs' solution (obtained by equimolar replacement of NaCl by KCl in the Krebs' solution), and the ring was considered viable and used for experiments only if two reproducible high-K þ contractions were obtained. 20,22 Vascular Reactivity Studies Endothelium-dependent and -independent relaxations were assessed by measuring the dilatory responses of mesenteric arteries to cumulative concentrations of acetylcholine (ACh; 10 À 10 -10 À 5 mol/l) and sodium nitroprusside (SNP; 10 À 10 -10 À 5 mol/l), respectively. All experiments were performed in vessels pre-contracted with phenylephrine (PE; 10 mmol/l).…”
Section: Mesenteric Artery Preparation and Isometric Tension Measurementmentioning
confidence: 99%
“…19,20 Organ chambers (2-ml volume) were filled with the Krebs' solution (37 1C and gassed with 95% air and 5% CO 2 ; pH 7.4). Each ring was mounted on two L-shape stainless-steel holders, one of which was fix to the organ bath and the other connected to a force displacement transducer (Beijing Aeromedicine Engineering Research Institute, Beijing, China) attached to a Taimeng BL-420 biotic signal collection and analysis system (Taimeng Instruments, Chengdu, China) for continuous recording of isometric tension.…”
Section: Mesenteric Artery Preparation and Isometric Tension Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Recently, we reported that myocardial infarction caused endothelial dysfunction in rat aorta, 64 and Zhao et al showed that myocardial IR produced endothelial dysfunction in mesentery vessels. 51 Accordingly, endothelial dysfunction was studied in the coronary circulation and the aorta of rat hearts with IR. At both sites, there was marked endothelial dysfunction, as reflected by the attenuated vasodilatory response to acetylcholine after IR.…”
Section: Discussionmentioning
confidence: 99%